2019
DOI: 10.1108/ilt-10-2018-0394
|View full text |Cite
|
Sign up to set email alerts
|

Flow characteristics of a hydraulic cone-throttle valve during cavitation

Abstract: Purpose This paper aims to resolve the cavitation problem encountered in cone throttle valves concerning fluid flow performance and pitting from cavitation luminescence, the author studied the flow field within a cone throttle valve set with various valve openings, inlet pressures and outlet back pressures. Design/methodology/approach The flow and cavitation distribution in the valve under different pressure conditions were obtained in simulations. To confirm these results experimentally, a hydraulic cavitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Viscosity is a measure of an oil thickness and ability to flow at certain temperatures, while viscosity index is a lubricating oil quality indicator, an arbitrary measure for the change of its kinematic viscosity with temperature and provides an insight into the oil's ability to perform at high and low temperatures (1)(2)(3)(10)(11)(12) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Viscosity is a measure of an oil thickness and ability to flow at certain temperatures, while viscosity index is a lubricating oil quality indicator, an arbitrary measure for the change of its kinematic viscosity with temperature and provides an insight into the oil's ability to perform at high and low temperatures (1)(2)(3)(10)(11)(12) .…”
Section: Resultsmentioning
confidence: 99%
“…The viscosity indices were also determined using the ASTM D 341 diagram, shown in Another indication of the change in kinematics viscosity with temperature, which is less arbitrary than the viscosity index, is the viscosity-temperature coefficient, VTC, defined by the relationship (1)(2)(3)11,12) V TC…”
Section: Methodsmentioning
confidence: 99%
“…The cavitation pressures calculated according to the molecular dynamics results were compared with the predictions produced using an existing mathematical model, and good agreement was obtained. Zhang et al [9] conducted experimental studies to visualize the evolution of cavitation bubbles near the wall using a nanosecond-micron space-time resolution laser photogrammetry system. They analyzed the morphological characteristics of cavitation bubble collapse at specific times and calculated the collapsed cavitation bubbles near the solid wall using the open FOAM program.…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al [31] numerically analyzed the cavitating flow in microchannels and the effects of the diameter ratio and pressure drop were discussed. Zhang [32] studied the flow characteristics of a cone throttle valve under cavitation, and the cavitation luminescence was used to help relative experiments. Yuan et al [33] compared the compressible and incompressible method, and their results showed that the compressible method could provide more precise results.…”
Section: Introductionmentioning
confidence: 99%